A comprehensive evaluation of radiation hardening by applying negative body bias and back-gate bias in 130 nm PDSOI technology. (February 2020) - Xie, Xin; Zhu, Huilong; Bi, Dawei; Hu, Zhiyuan; Ren, JiangChuan; Zhang, Haineng; Zhang, Zhengxuan; Zou, Shichang
Abstract: This paper comprehensively evaluates the effects of negative body bias and negative back-gate bias on the total ionizing dose (TID) effects in 130 nm partially-depleted (PD) SOI technology. We studied the T-gate/H-gate nMOSFETs and pMOSFETs, and found that the negative body bias is ineffective for radiation hardening. However, the negative back-gate bias is an effective method for hardening the nMOSFETs. When the back-gate is biased at −2.5 V during irradiation and measurement, the TID tolerance can be improved from below 50 krad(Si) to up 100 krad(Si) while the performance of pMOSFETs is not degraded. 3D TCAD simulations are performed to analyze the failure of the negative body bias and the effective mechanism of the negative back-gate bias. Highlights: We comprehensively studied the radiation hardening effect of the negative back-gate bias in 130nm PDSOI technology. We found the negative body bias is noneffective for hardening in 130nm PDSOI technology. By 3D TCAD simulations, we deeply interpret the mechanism of the radiation hardening effect of the negative back-gate bias. By 3D TCAD simulations, we interpret why there is no effect on hardening by the negative body bias. We proposed a method to further improve radiation hardening by negative back-gate bias in practice.